A novel approach to mapping and calculating the rate of spread of endemic bovine tuberculosis in England and Wales. (April 2015) - Brunton, L.A.; Nicholson, R.; Ashton, A.; Alexander, N.; Wint, W.; Enticott, G.; Ward, K.; Broughan, J.M.; Goodchild, A.V.
Abstract: A mathematical method for estimating the endemic status of bovine tuberculosis (bTB) in cattle in England and Wales has been developed. 6.25 km 2 hexagonal cells were used as the base resolution. Maps were produced for overlapping two-year periods spanning 2001/03 to 2009/11. Distance from a farm to the ten nearest 'Officially Tuberculosis Free status – Withdrawn' incidents within the same time period was measured. Endemic areas were defined as those hexagons containing farms where the 3rd nearest incident occurred within 7 km. Temporal spread of endemic bTB was estimated by creating a contour map displaying the spread of endemic bTB over the two-year periods, and using boundary displacement to calculate the rate of spread across each hexagon. A rate was obtained for ∼2300 cells and varied between 0.04 km and 15.9 km per year (median = 3.3 km per year). This work will enable further analysis of the factors associated with this expansion.